Indoor air quality at school: ventilation rates and it impacts towards children: a review - Muhamad Salleh, N.; Kamaruzzaman, S.N.; Sulaiman, R.; Mahbob, N.S. (2011)
The reviews on the subject of school environments emphasized that indoor air quality (IAQ) is often inadequate in classrooms causing increased risk for asthma and other health-related symptoms in preschool environment. It is most pronounced in developed countries. The paper summarizes and explores the peer-reviewed literature on IAQ in schools environment and to explicit the importance of IAQ in school’s environment by reviewing the previous studies on exposure of pupils towards poor IAQ in the classrooms. The existing reviewed data emphasizes on impact of Ventilation Rates and CO2, on children‘s health and performance while performing assessment on existing standards (ASHRAE, NIOSH, ACGIH and OSHA). The study found that, most of the children are exposed to the inadequate environment during their time in the classroom which is not complying with the established standard. Expectantly, this paper is comprehensive to determine the sufficient information and as a reference for further data collection to assess the IAQ in Malaysian’s schools.